Dynamics of productive investment and gaps between the United States and EU countries - Doris Hanzl-Weiss; Robert Stehrer (European Investment Bank (EIB), 2024)
This report offers a detailed documentation and assessment of the differences in real productive investment between the United States and EU countries, focusing especially on the period 2013-2019. The analysis is based on capital stock and gross fixed capital formation (GFCF) data taken from Eurostat and the recent EU KLEMS releases, which provide comparable data for the US. The study considers various measures: investment gaps (defined as the difference in investment rates); the growth of real GFCF; and the accumulation of stocks. It documents differences in trends and in asset-type composition, as well as variations across the different EU countries. The study thus brings the existing literature up to date and adds investment dynamics to the discussion. The findings indicate the existence of a gap in productive investment in the period since the onset of the global financial crisis (caused largely by lower rates of investment, specifically in tangible information and communication technology and intangible assets) and gaps for larger EU member states. When we consider investment dynamics, we find more robust growth rates in productive investment in the EU than in the US over this period; however, again investment was lower in telecommunications equipment and software and databases. Since growth rates in the EU27 and the US have been similar since 2013, the EU27 has been unable to catch the US up in terms of capital accumulation. However, these results are sensitive to the application of asset price deflators: when US deflators are applied to the EU27, the differences are much less significant.
Keywords: E22; 330; Productive investment; investment gap; investment dynamics; European Union; US